EKSPLORASI RIGGING PADA KARAKTER 3D AMICO - Wijaya, Wisnu; Ramadhani, Nugrahardi (Program Studi Desain Komunikasi Visual, 2024)
A spherical robot named Amico serves as the mascot for the 63rd anniversary celebration of ITS. Amico's design as a sphere embodies a concept of greater flexibility compared to other geometric objects, representing high mobility. The challenge lies in configuring the rigging of the spherical object to move in all directions (X, Y, and Z axes) without distorting the three-dimensional model. The method used involves experimentation with adding parameter properties to selected bones. The complexity of rigging varies according to specific needs of each 3D character. To avoid gimbal lock, where two rotational axes become aligned, complicating rotation for animators, particularly for ball-based 3D characters, multiple layers of bone hierarchy are used. Creating multiple layers of hierarchical control helps reduce the likelihood of gimbal lock. Parameter properties offer more control options for 3D objects. In terms of time efficiency, these parameters automate certain aspects of animation, such as scale changes and geometric shape alterations, regardless of the object's movement and rotation. These changes make the visualization of 3D objects appear more dynamic by adhering to animation principles such as stretch and squash. Simply put, parameter properties serve as centralized controls, allowing animators to manage and coordinate multiple elements from a single point (parameter properties), thus making control management and coordination more efficient.